PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MATERI SIKLUS AIR DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Zahra, Fatimahtu; Aprilia, Rapita; Kumala Sari, Cut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The goal of this project is to create an animated film about the water cycle for use in primary school science classes. The purpose of this study was to determine the outcomes of practicality as well as the validation of material experts, language experts, and media experts. Analysis (Analysis), Design (Planning), Development (Development), Implementation (Implementation), and Evaluation (Evaluation) are the five stages of the ADDIE model, which is the sort of R&D used in this study. Observation, interviews, expert validation questionnaires, and student and teacher response surveys are the methods utilized to gather data. Linguists received a percentage of 97.7% with the criteria "very worthy," media experts received a percentage of 85% with the criteria "very eligible," and material experts received a percentage of 75% with the criteria "feasible." The practicality of the teacher's response received a percentage of 98.3% with the criteria "very practical," and the practical results of the student response questionnaire achieved a percentage of 90% with the criteria "very practical" in limited trials. It is clear from the evaluation of the learning media animation video that it is very viable for usage as learning media.